Ответы 3

  • Спасибо
    • Автор:

      nyasia
    • 5 лет назад
    • 0
  •  - 3 \frac{1}{2} - ( - x + \frac{5}{2}) = - \frac{7}{2} + x - \frac{5}{2} = \\ = х - \frac{12}{2} = х - 6 \\ x = - \frac{1}{2} \\ - \frac{1}{2} - 6 = - 6 \frac{1}{2}
    • Автор:

      walton
    • 5 лет назад
    • 0
  •         1x= - —        2       1           5           1(- 3 —)-(-x+ —)= - 6 —       2           2           2     1      5     6                                    1                 11) — + — = — = 3                 2) (- 3 —) - 3 = - 6 —     2      2      2                                   2                 2
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years